FGF23 (Fibroblast Growth Factor-23) and Incident Hypertension in Young and Middle-Aged Adults: The CARDIA Study. Issue 1 (July 2018) - Akhabue, Ehimare; Montag, Samantha; Reis, Jared P.; Pool, Lindsay R.; Mehta, Rupal; Yancy, Clyde W.; Zhao, Lihui; Wolf, Myles; Gutierrez, Orlando M.; Carnethon, Mercedes R.; Isakova, Tamara
Abstract : Blacks have the highest prevalence of hypertension in the United States. Higher levels of FGF23 (fibroblast growth factor-23) have been associated with worse cardiovascular outcomes. Whether FGF23 is associated with rising blood pressure (BP) and racial differences in incident hypertension is unclear. We studied 1758 adults (45.0±3.7 years; 57.8% female; 36.9% black) without hypertension or cardiovascular disease who participated in the year 20 (2005–2006) follow-up examination of the CARDIA study (Coronary Artery Risk Development in Young Adults). We investigated the associations of baseline (year 20) cFGF23 (C-terminal FGF23) levels with longitudinal BP patterns and incident hypertension (defined as being on antihypertensive medication, systolic BP ≥130 or diastolic BP ≥80 mm Hg) during 2 follow-up visits (years 25 and 30). During follow-up, 35.2% of participants developed hypertension. In multivariable linear mixed models, there were greater increases in systolic BP from year 20 to 25 and year 25 to 30 in the highest FGF23 quartile relative to the lowest quartile (+2.1 mm Hg, P =0.0057 and +2.2 mm Hg, P =0.0108, respectively for each time period), whereas there were greater increases in diastolic BP from year 20 to 25 in the highest quartile relative to the lowest (+1.6 mm Hg; P =0.0024). In multivariable modified Poisson regression analyses, the highest FGF23 quartile was associated with a 45% greater risk of developing hypertension during follow-up compared with the lowest quartile (relative risk, 1.45 [1.18–1.77]). Results did not vary by race ( P interaction =0.1523). Higher FGF23 levels are independently associated with rising BP over time and an increased risk of incident hypertension but not racial differences in hypertension. Abstract : Supplemental Digital Content is available in the text.